Change of Aluminum Concentrations in Specific Plants by Species, Organ, Washing, and Traffic Density - Kuzmina, Nadezda; Menshchikov, Sergey L.; Mohnachev, Pavel; Zavyalov, Konstantin E.; Petrova, Irina V.; Ozel, Halil Baris; Sevik, H. (North Carolina State University, 2023)
One of the most critical problems throughout the world is air pollution, causing the death of millions of individuals annually, and it is reported that 90% of the global population breathes polluted air. Among the components of air pollution, the most harmful ones are the heavy metals, which can remain non-degraded in nature for a long time, bio-accumulate in living organisms, and be toxic or carcinogenic at low concentrations. Hence, monitoring and reducing heavy metal pollution in the air are high-priority research topics. Heavy metals can accumulate within various organs of plants grown in an environment with an increased level of heavy metal pollution. The metal analyses on these organs can provide insight into the heavy metal pollution in the air. In the present study, the concentrations of aluminum (Al), one of the most important heavy metals, were determined in the different organs of five plant species grown in regions with different traffic densities. Remarkable changes were observed in the Al concentrations in all the organs of species, which were examined here by organ and traffic density. The highest values were obtained from the organs of plants grown in no-traffic regions. © 2023, North Carolina State University. All rights reserved.
Keywords: Air pollution; Al; Aluminum; Biomonitor; Heavy metal